An ice core derived 1013-year catchment-scale annual rainfall reconstruction in subtropical eastern Australia - C. R. Tozer; T. R. Vance; J. L. Roberts; A. S. Kiem; M. A. J. Curran; A. D. Moy (Hydrology and Earth System Sciences, 2016)
Paleoclimate research indicates that the Australian instrumental climate record (∼ 100 years) does not cover the full range of hydroclimatic variability that is possible. To better understand the implications of this on catchment-scale water resources management, a 1013-year (1000–2012 common era (CE)) annual rainfall reconstruction was produced for the Williams River catchment in coastal eastern Australia. No high-resolution paleoclimate proxies are located in the region and so a teleconnection between summer sea salt deposition recorded in ice cores from East Antarctica and rainfall variability in eastern Australia was exploited to reconstruct the catchment-scale rainfall record. The reconstruction shows that significantly longer and more frequent wet and dry periods were experienced in the preinstrumental compared to the instrumental period. This suggests that existing drought and flood risk assessments underestimate the true risks due to the reliance on data and statistics obtained from only the instrumental record. This raises questions about the robustness of existing water security and flood protection measures and has serious implications for water resources management, infrastructure design and catchment planning. The method used in this proof of concept study is transferable and enables similar insights into the true risk of flood/drought to be gained for other paleoclimate proxy poor regions for which suitable remote teleconnected proxies exist. This will lead to improved understanding and ability to deal with the impacts of multi-decadal to centennial hydroclimatic variability.